The application of adult education principles to school-based curriculum changes: a case study of a school-based curriculum change for Hebrew literature at a Jewish day school (Grades 8-9) in Johannesburg - Herman, Chaya (My University, 2014)
This case study explores, through critical reflection, the process of a school-based curriculum change (SBCC) and examines to what extent the application of adult education principles facilitates this process. The change is related to three issues: the process of curriculum development; the shift towards professional development based on adult education principles; and the changing role of the consultant in relation to curriculum development. Tire consultant came to realize that in order to promote school based curriculum development it was necessary to work with the head of the department and the teachers in a participative mode, rather than taking a stand as a curriculum development expert. The research findings suggest that in order to apply adult education principles to teachers’ professional development, the consultant needs to move from consultancy based on an expert role towards consultancy based on a process role. The research proposes that professional development based on adult education principles and teamwork could be a promising introduction to a secondorder change promoting a school culture of teamwork and critical reflection. The researcher came to question the appropriateness of a case study based on participant observation as a research methodology in the workplace. She suggests that an action research could be more advantageous to promote a second-order change and could be more in line with adult education principles.
Thesis (M.Ed.)--University of the Witwatersrand, Faculty of Education, 1998.
Keywords: adult education; school-based curriculum development; professional development; consultants; change; critical reflection; case studies